2018
DOI: 10.1111/apa.14521
|View full text |Cite
|
Sign up to set email alerts
|

General intelligence was associated with academic achievement but not fitness in adolescents after one year

Abstract: General intelligence may not predict fitness, but it may predict academic achievements in adolescents one year later. Further studies are needed to examine our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…However, the literature regarding physical fitness and intelligence in youth is scarce, and little is known about the relationship between them. Longitudinally, within the same cohort used in the present study, we concluded that general intelligence may not predict physical fitness, but it may predict better academic achievement in adolescents one year later [9]. However, we found very little information showing the association between physical fitness components and general intelligence in adolescents.…”
Section: Introductioncontrasting
confidence: 58%
See 2 more Smart Citations
“…However, the literature regarding physical fitness and intelligence in youth is scarce, and little is known about the relationship between them. Longitudinally, within the same cohort used in the present study, we concluded that general intelligence may not predict physical fitness, but it may predict better academic achievement in adolescents one year later [9]. However, we found very little information showing the association between physical fitness components and general intelligence in adolescents.…”
Section: Introductioncontrasting
confidence: 58%
“…This study was part of the "Cognitive performance, academic achievement and fitness: Longitudinal and cross-sectorial" project (reference number PIV-006/17). The aim of this project was to examine the relationship between physical fitness, cognition and academic achievement in adolescents from the south of Spain [9,17]. For this study, we used cross-sectional data.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this perspective offers important practical contributions at different levels at school that should be taken into consideration by schools' administrators and teachers. For example, there is commonly only little time in schools allocated to sports activities due to the pressure for academic achievement (also with respect to e.g., school's rankings; competition; grades competition to access specific Universities/courses), as well as to greater quantity of lesson for studying the subjects [6]. Our results support that school policies that aim to develop the overall concept of physical fitness may increase academic achievement.…”
Section: Discussionsupporting
confidence: 70%
“…Physical fitness is a set of individual's attributes related to the ability to perform physical activity and exercise [1] that have been associated with healthy physical and mental conditions throughout the lifespan [2,3]. Despite the fact that there is a remarkable amount of studies reporting a positive relationship between physical fitness and physical health in children and adolescents [3][4][5], much more detailed research is still needed to better understand the impact of a healthy physical fitness profile on brain development, functioning, plasticity, and cognition, which could finally also determine children's and adolescent's academic achievement [6][7][8]. From this framework, physical fitness has a beneficial effect on academic achievement due to a complex network phenomenon based on the effects of neural substrates that are linked to improvements in brain structure, brain function, and brain connectivity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%